2022
DOI: 10.1101/2022.04.18.488621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organelle-selective click labeling coupled with flow cytometry allows high-throughput CRISPR screening of genes involved in phosphatidylcholine metabolism

Abstract: Lipids comprise biomembranes and are involved in many crucial cell functions. While cellular lipid synthesis and transport appear to be governed by intricate protein networks, the whole scheme is insufficiently understood. Although functional genome-wide screening should contribute to deciphering the regulatory networks of lipid metabolism, technical challenges remain – especially for high-throughput readouts of lipid phenotypes. Here, we coupled organelle-selective click labeling of phosphatidylcholine (PC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…52−55 The alkyne-or azide-bearing PC analogues labeled via the Kennedy pathway are distributed in essentially all membranes without appreciable selectivity, 47,49 but organelle-targeting clickable dyes can be used to visualize subsets of azido PC analogues in specific organelle membranes, including the PM, ER, and mitochondria. 56,57 Beyond the Kennedy pathway, we showed that an alkynyl choline derivative can also be converted to the corresponding PC analogue through a single PLD transphosphatidylation step (Figure 6B). 37 Because PLD activity can be controlled by external stimuli to activate endogenous PLDs or via exogenous optoPLDs, we envisioned that diverse bioorthogonal choline analogues might permit differential organelle labeling if installed selectively by PLD enzymes.…”
Section: ■ Beyond Pa: Phosphatidylcholine As a Target For Super-resol...mentioning
confidence: 99%
“…52−55 The alkyne-or azide-bearing PC analogues labeled via the Kennedy pathway are distributed in essentially all membranes without appreciable selectivity, 47,49 but organelle-targeting clickable dyes can be used to visualize subsets of azido PC analogues in specific organelle membranes, including the PM, ER, and mitochondria. 56,57 Beyond the Kennedy pathway, we showed that an alkynyl choline derivative can also be converted to the corresponding PC analogue through a single PLD transphosphatidylation step (Figure 6B). 37 Because PLD activity can be controlled by external stimuli to activate endogenous PLDs or via exogenous optoPLDs, we envisioned that diverse bioorthogonal choline analogues might permit differential organelle labeling if installed selectively by PLD enzymes.…”
Section: ■ Beyond Pa: Phosphatidylcholine As a Target For Super-resol...mentioning
confidence: 99%
“…Another recent example of using bioorthogonal labeling and CRISPR screening came from Tsuchiya et al, who applied an organelle-selective click chemistry labeling of the abundant phospholipid phosphatidylcholine (PC), followed by flow cytometry with CRISPRko screens, to identify regulators of PC biosynthesis and transport. [63] In this screen, CRISPRperturbed cells were metabolically labeled with an azidocholine analog to generate azido-functionalized PC lipids within several organelle membranes. Using cyclooctyne-fluorophore dyes which were targeted to specific organelle compartments, the azido-PC could be selectively tagged.…”
Section: Fluorescence-activated Cell Sorting (Facs)mentioning
confidence: 99%
“…Instead, a different strategy involves covalent tagging of abundant lipid constituents of membranes using metabolic labeling and bioorthogonal chemistry. , Notably, phosphatidylcholine (PC) is an attractive target because it is the most abundant molecule in eukaryotic membranes. , Indeed, metabolic labeling of PC was first achieved using propargylcholine, an alkynyl analogue of choline, which is biosynthetically converted to PC via the multistep Kennedy pathway. , Propargylcholine labeling produces alkynyl PC, which can be visualized in fixed cells by Cu-catalyzed azide–alkyne cycloaddition (CuAAC) tagging with azide-bearing fluorophores . For live-cell imaging, fluorescent PC derivatives can be generated by metabolic labeling with an azidocholine analogue ( 1 , Figure A) followed by strain-promoted azide–alkyne cycloaddition (SPAAC) tagging with cyclooctyne-fluorophores .…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Indeed, metabolic labeling of PC was first achieved using propargylcholine, an alkynyl analogue of choline, which is biosynthetically converted to PC via the multistep Kennedy pathway. 14 , 15 Propargylcholine labeling produces alkynyl PC, which can be visualized in fixed cells by Cu-catalyzed azide–alkyne cycloaddition (CuAAC) tagging with azide-bearing fluorophores. 16 For live-cell imaging, fluorescent PC derivatives can be generated by metabolic labeling with an azidocholine analogue ( 1 , Figure 1 A) followed by strain-promoted azide–alkyne cycloaddition (SPAAC) tagging with cyclooctyne-fluorophores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation